Bacterial Load Comparison of the Three Main Lineages of Mycobacterium tuberculosis Complex in West Africa - Osei-Wusu, Stephen; Morgan, Portia; Asare, Prince; Adams, Godfrey; Musah, Abdul Basit; Siam, Ishaque Mintah; Gillespie, Stephen Henry; Sabiiti, Wilber; Yeboah-Manu, Dorothy (Frontiers in Microbiology, 2021)
Studies have shown an association between bacterial load and virulence; however, not much is known about the diversity in this phenotypic characteristic of Mycobacterium tuberculosis complex (MTBC). This study was therefore aimed to determine the differences in bacterial load of the three most prevalent MTBC genotypes (L4, L5 and L6) in West Africa at the time of diagnosis. A total of 170 paired fresh sputum samples were collected; one part in guanidinium thiocyanate (GTC) was used for RNA extraction and tuberculosis Molecular Bacterial Load Assay (TB-MBLA) and the other part without GTC was confirmed for TB positivity using Gene Xpert MTB/RIF, smear microscopy grading and culture on Löwenstein-Jensen media slants. The 170 sputum samples comprised of 155 new cases, 3 follow-up cases and 12 TB negative sputum samples. The time-to-culture-positivity (TTP) and degree of culture positivity (DCP) were recorded. All 122 isolates obtained were Spoligotyped for lineage (L) classification but spoligotypes were obtained from 120 isolates. Of the typed isolates, 70.0%, 10.8%, 10.8%, 4.2%, 2.5%, 0.8% and 0.8% were Lineage- 4, 5, 6, 2, 3, 1, and M. bovis respectively. Further analysis of the three most prevalent lineages showed significantly shorter TTP and higher DCP by L4 compared to L5 and L6 respectively: TTP 20.8, versus 26.5, and 28.2 days; p-value=0.005 and DCP 1.27, versus 0.81 and 0.29, p<0.001. Average TB-MBLA measured bacterial load of L4 was 3.82 Log10eCFU/mL which was not significantly different from 3.81 and 3.80 Log10eCFU/mL of L5 and L6 respectively, p=0.84. Degree of smear microscopy: L4=1.20, L5=1.20, L6=0.92 and Gene Xpert Cq values: L4=17.08, L5=18.37, L6=17.59; showed no significant difference between the lineages, p=0.72 and p=0.48 respectively. Retrospective analysis of a larger sample confirmed the difference in TTP, p<0.001. In conclusion, the observed shorter TTP and high DCP of L4 could signify high growth rate in culture that is independent of total bacterial load at diagnosis.